ANALISIS PENERAPAN LITERASI NUMERASI DALAM PEMBELAJARAN TEMATIK DI MIN 1 JOMBANG - Shabirah, Shafa; Mahsun, Ali (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
Numeracy literacy in thematic learning involves combining numeracy in various subjects with methods and approaches that make it easier for students. It teaches students to understand and apply numeracy in everyday life, so it is important to integrate it in thematic learning. This research aims to examine the application of numeracy literacy in thematic learning in class 2 of MIN Jombang. Using a qualitative approach with case studies, data was collected through observation, interviews and documentation. Data analysis involves data reduction, data presentation, and verification to ensure validity with careful observation, triangulation of sources and techniques, and material references. The results of research on the Application of Numeracy Literacy in Thematic Learning in Class 2 MIN 1 Jombang, are that the application of numeracy literacy in thematic learning in class 2 MIN 1 Jombang has been implemented well by the school. The habit that is carried out is reading 15 minutes before learning to foster students' interest in reading. Then the methods most widely used in the learning process are project based and collaborative learning.